InAs raised buried oxide SOI-TFET with N-type si1-xgex pocket for low-power applications - Singh A.K.; Jit S. (My University, 2025)
In this chapter, we studied the device-level performance based on electrostatic parameters of a source pocket engineered raised buried oxide (RBOX) SOI tunnel field-effect transistor (SP-RBOX-SOITFET). Using Si1-xGex pockets between the channel and the source, steep subthreshold swing transistors can be obtained. In the pocket, a narrow n+ region is formed by a tunneling junction between the p+ region of the source. In order to reduce subthreshold swing, the tunneling width must be narrowed, and the lateral electric field must be increased. So, the studied structure can be used to design the dielectric modulated biomolecule biosensors for IOTs applications. Simulation analyses of the proposed work has been conducted using the Silvaco ATLAS TCAD tool. © 2024 Bentham Science Publishers. All rights reserved.